1997
DOI: 10.1111/j.1600-0676.1997.tb01023.x
|View full text |Cite
|
Sign up to set email alerts
|

Platelet‐associated IgM elevated in patients with chronic hepatitis C contains no anti‐platelet autoantibodies

Abstract: associated IgM elevated in patients with chronic hepatitis C contains no anti-platelet autoantibodies.Abstract: We investigated whether thrombocytopenia in patients with chronic hepatitis C is due to anti-platelet autoantibodies. Platelet-associated IgG (PAIgG j and platelet-associated IgM (PAIgM) were measured by direct immunofluorescent flow cytometric analysis. Elevation of PAIgM level was detected in 70% of chronic hepatitis C patients, while only a mild elevation of PAIgG level was detected in 32% of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 24 publications
1
5
0
Order By: Relevance
“…Various authors confirmed these findings, calling attention to the nonspecific character in relation to the cause of the event [21,22,23]. Other studies found an alteration in platelet adhesion function, which is evidenced earlier than aggregation defects, that in general are delayed, as demonstrated in the test of platelet function in patients with chronic hepatic insufficiency [24,25].…”
Section: Clinico-epidemiological Manifestationssupporting
confidence: 53%
“…Various authors confirmed these findings, calling attention to the nonspecific character in relation to the cause of the event [21,22,23]. Other studies found an alteration in platelet adhesion function, which is evidenced earlier than aggregation defects, that in general are delayed, as demonstrated in the test of platelet function in patients with chronic hepatic insufficiency [24,25].…”
Section: Clinico-epidemiological Manifestationssupporting
confidence: 53%
“…Antibody‐mediated thrombocytopenia has been assumed to be due to increased levels of platelet‐associated IgG or IgM (15, 33, 34). In contrast to AITP patients, eluates from platelets of HCV‐infected patients do not react with donor platelets (35), suggesting that immune complexes, rather than antibodies, were responsible for platelet‐associated immunoglobulins IgM (36). The MAIPA technique, however, is not influenced by the presence of immune complexes (37, 38), and it is therefore unlikely that our results are adulterated by the detection of immune complexes.…”
Section: Discussionmentioning
confidence: 99%
“…All serum samples were negative for HIV antibodies and HBsAg using a standard enzyme immunoassay technique. Platelet-associated antibodies were determined by immunot1uorescent flow cytometric analysis, as previously described by Li et al' 6 Abdominal ultrasound and portal power Doppler was performed in all patients at presentation to rule out hypersplenism and/or portal hypertension. Percutaneous liver biopsy was performed in all patients and evaluated according to the Ishak score.…”
Section: Methodsmentioning
confidence: 99%
“…The pathogenic mechanism of the thrombocytopenia in these patients has not been fully explained, but in at least some cases thrombocytopenia could be caused by an immune mechanism as a result of hepatitis C virus infection 1,4,5 . Some studies on patients with chronic HCV infection have pointed out the possible association between thrombocytopenia and elevated titres of platelet‐associated immunoglobulin G and/or antiphospholipid antibodies 4–8 …”
mentioning
confidence: 99%